Evolution of Alzheimer's Disease Cerebrospinal Fluid Biomarkers in Early Parkinson's Disease. Issue 3 (2nd July 2020) - Irwin, David J.; Fedler, Janel; Coffey, Christopher S.; Caspell‐Garcia, Chelsea; Kang, Ju Hee; Simuni, Tanya; Foroud, Tatiana; Toga, Arthur W.; Tanner, Caroline M.; Kieburtz, Karl; Chahine, Lana M.; Reimer, Alyssa; et al.
Abstract : Objective: We analyzed the longitudinal profile of Alzheimer's disease (AD) cerebrospinal fluid (CSF) biomarkers in early Parkinson's disease (PD) compared with healthy controls (HCs) and tested baseline CSF biomarkers for prediction of clinical decline in PD. Methods: Amyloid‐β 1 to 42 (Aβ42 ), total tau (t‐tau) and phosphorylated tau (p‐tau) at the threonine 181 position were measured using the high‐precision Roche Elecsys electrochemiluminescence immunoassay in all available CSF samples from longitudinally studied patients with PD (n = 416) and HCs (n = 192) followed for up to 3 years in the Parkinson's Progression Markers Initiative (PPMI). Longitudinal CSF and clinical data were analyzed with linear‐mixed effects models. Results: We found patients with PD had lower CSF t‐tau (median = 157.7 pg/mL; range = 80.9–467.0); p‐tau (median = 13.4 pg/mL; range = 8.0–40.1), and Aβ42 (median = 846.2 pg/mL; range = 238.8–3, 707.0) than HCs at baseline (CSF t‐tau median = 173.5 pg/mL; range = 82.0–580.8; p‐tau median = 15.4 pg/mL; range = 8.1–73.6; and Aβ42 median = 926.5 pg/mL; range = 239.1–3, 297.0; p < 0.05–0.001) and a moderate‐to‐strong correlation among these biomarkers in both patients with PD and HCs (Rho = 0.50–0.97; p < 0.001). Of the patients with PD, 31.5% had pathologically low levels of CSF Aβ42 at baseline and these patients with PD had lower p‐tau levels (median = 10.8 pg/mL; range = 8.0–32.8) compared with 27.7% of HCs with pathologically low CSF Aβ42 (CSF p‐tau median = 12.8 pg/mL; range 8.2–73.6; p < 0.03). In longitudinal CSF analysis, we found patients with PD had greater decline in CSF Aβ42 (mean difference = −41.83 pg/mL; p = 0.03) and CSF p‐tau (mean difference = −0.38 pg/mL; p = 0.03) at year 3 compared with HCs. Baseline CSF Aβ42 values predicted small but measurable decline on cognitive, autonomic, and motor function in early PD. Interpretation: Our data suggest baseline CSF AD biomarkers may have prognostic value in early PD and that the dynamic change of these markers, although modest over a 3‐year period, suggest biomarker profiles in PD may deviate from healthy aging. ANN NEUROL 2020;88:574–587